Rate of approximation of blending type modified univariate and bivariate λ-Schurer-Kantorovich operators - Reşat Aslan (Kuwait Journal of Science)
In this work, we investigate some approximation properties of blending type univariate and bivariate Schurer-Kantorovich operators based on shape parameter λ ∈ [−1, 1]. We evaluate some moment estimates and obtain several direct theorems. Next, we construct the bivariate version of proposed operators and compute rate of approximation with the partial and complete modulus of continuity. Moreover, we present certain graphical and numerical results for univariate and bivariate versions of these operators.